UTILIZATION OF TECHNOLOGY-BASED LEARNING MEDIA IN IMPROVING STUDENTS' LEARNING INTEREST IN INDONESIAN LANGUAGE LESSONS IN GRADE I OF STATE ELEMENTARY SCHOOL 22 BANDA ACEH: Utilization Of IT Learning Media - Aslamiah Tuti (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Abstract This study aims to determine the form of use of digital learning media in increasing student interest in learning at SD Negeri 22 Banda Aceh. This type of research is qualitative research and a descriptive approach. The subjects of the study were students of class Ib of SD Negeri 22 Banda Aceh, while the data collection techniques used interview, observation, and documentation techniques. The results of this study indicate that: 1) The form of use of digital learning media in increasing student interest in learning at SD Negeri 22 Banda Aceh, namely in the form of power point, Canva design, and wordwall. 2) The implementation of learning by utilizing technology-based learning media provides very good things, especially in terms of utilizing more practical learning, more optimal use of time and easier and more varied use of materials. So that students are very enthusiastic in the learning process. (3) The use of information technology media has a positive impact on the learning process of students in increasing interest in learning in the learning process. In addition to being fun, it can also arouse motivation, enthusiasm in participating in learning at school. (4) From the results of interviews and observations conducted with students, by utilizing information technology-based learning media, there is an increase in student interest in learning, especially class Ib, students are very motivated in participating in learning. The enthusiasm that arises in students because the materials and media used are more interesting, more active, more effective and the learning is more varied.